Organic semiconductor photosensors - Ocaya, R. O.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2017)
Coumarin doped with poly(3-hexylthiophene)/p-Si photodiodes were prepared by the drop-casting technique. The current voltage characteristics of the prepared diodes with the structure of All P3HT:Coumarin/p-Si/Al diodes were investigated under dark and various illumination intensities using both I-V and C-V methods. Using both illuminated DC and transient I-V and C-V measurements, the photocurrents are shown to depend on light intensity with the P3HT:Coumarin ratio influencing photoresponsivity. The photocurrents increase with increasing illumination intensity. C-V measurements show that the capacitance of the diode depends on voltage, frequency and illumination, indicating the existence of a continuous distribution of interface states that can be described in terms of organic organic polymer blend domains in additional to the well studied metal-semiconductor interface states. The best responses were found to be for the diode having 10% Coumarin weight. These results suggest that the Al-p-Si/P3HT:Coumarin/Al diode can be used as a photosensor. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: P3HT:Coumarin; Organic semiconductors; Photodiode